Struktura zależności a miary ryzyka na przykładzie indeksów giełd światowych i GPW w Warszawie - Papla, Daniel (Dependence Structure and Risk Measures on the Example of Indexes of World Stock Markets and Warsaw Stock Exchange, 2009)
Research hypothesis of this paper is as follows: misspecified model of dependency between elements of financial assets portfolio may lead to errors in risk evaluation measured by such measures like Value at Risk (VaR) or Conditional Value at Risk (CVaR). In the case of research included in this paper several copula functions were used to verify research hypothesis as a model of dependence structure. Goodness of fit obtained with each parametric copula was measured with Anderson-Darling, Integrated Anderson-Darling and entropy test (with use of empirical copula). The research hypothesis was verified by Monte-Carlo simulation o Value at Risk using copula function parameter estimation for each pair of stock market indexes. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 390-397